Control of seed-to-seedling transition by an upstream open reading frame in ABSCISIC ACID DEFICIENT2 - Zhen Wang; Xiaofan Zhang; Can Zhou; Xiaofeng Cao (Proceedings of the National Academy of Sciences, 2025)
The start of seed germination is a major decision point in plant life cycle, which relies on seed stored mRNA. However, the underlying translational mechanism remains less illustrated. Here, we demonstrate that inhibiting translation using translation inhibitors and ribosome-defective mutants delays germination in Arabidopsis . Through comprehensive transcriptome deep sequencing (RNA-seq) and polysome profiling analyses, we elucidated the dynamic interplay of regulation at the transcriptional and translational levels during germination. We show that delayed germination in some ribosome-defective mutants is partially regulated by the gene ABSCISIC ACID DEFICIENT2 ( ABA2 ), with an upstream open reading frame (uORF) in the 5′ untranslated region that represses translation of the downstream ORF encoding ABA2. In addition, disrupting rice OsABA2 uORF inhibited preharvest sprouting (PHS). Furthermore, we found two main haplotypes for the uORF among rice cultivars that result in different OsABA2 expression levels, thus contributing to diverse PHS phenotypes. This work highlights the critical role of translational control and genetic variation in seed dormancy and germination, with implications for crop improvement.